Effect of Warm Water Foot Bath on Post Dialysis Fatigue in patients on Maintenance Hemodialysis - Akhtar Zeb, Muhammad Iqbal, Aurangzeb, Nasir Anwar, Muhammad Suliman, Amir Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effectiveness of warm water foot bath therapy on post dialysis fatigue. Method: A Quasi experimental single group (pre and post-test) design was conducted in Nawaz Sharif Kidney Hospital, Swat. Single time intervention was provided to sixty (60) participants recruited through consecutive sampling technique. Demographic data were collected through self-structured interview and fatigue level was measured using Piper’s Fatigue Scale before and after foot bath therapy. The data were interred and analyzed through SPSS. Paired t-test was used to find out differences in mean while chi-square test was applied for association of fatigue score on the basis demography. To evaluate the effectiveness of the intervention paired t-test was calculated. Results: Cumulative pre-intervention fatigue score was 47.33±12.8 and post intervention cumulative fatigue score was 29.9±9.8. Mean of Pre-fatigue score of different groups made on the basis of demographic characteristics were not statistically different. Pre intervention individual mean fatigue sore was 5.25±142 while the post intervention was 3.33±1.09. A significant difference (P valve 0.000) was found between pre and post intervention individual mean fatigue score. Conclusion: Result of the study suggested that warm water foot bath therapy had therapeutic effects in decreasing post dialysis fatigue. It provides relief and promotes comfort level of the patients. Keywords: Nurses, hemodialysis, Fatigue, warm water foot bath